Pengaruh Efikasi Diri dan Lokus Kendali (Locus of Control) Terhadap Prestasi Belajar Matematika - Anggi Ajeng Widyaninggar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
The purpose of this study was to analyze the influence of self-efficacy and locus of control on achievement of learning Mathematics. The method used was a survey. The sample size of 100 students in East Jakarta Regular SMAN randomly selected. Data collection is carried out by questionnaire and test engineering materials semester class X. Data analysis with path analysis techniques. The statistical test used t-test and SPSS. From the results of the study found that: (1) There is no direct effect of self-efficacy to locus of control with tcount = 0.8376 < ttable = 1.98; (2) There is a direct effect of self- efficacy to learning achievement Mathematics with tcount = 2.3148 < ttable = 1.98; (3) There is no direct effect of locus of control to learning achievement Mathematics with tcount = 1.8724 < ttable = 1.98; (4) There is no direct effect of self-efficacy to to learning achievement Mathematics through locus of control with tcount = -0.155 < ttable = 1.98.